Multipotentiality of the cellular population of human dental pulp through flow cytometry - Alcalá-Benites, Maritza (2018)
Objective: To determine, the multipotentiality of the cell population of human dental pulp by flow cytometry. Materials and methods: A descriptive, cross-sectional and prospective study was carried out in the cell population of 04 teeth of patients who attended at the Dental Center of the University of San Martín de Porres. The patients were informed of the present study and signed the voluntary donation consent of their extracted teeth. The sample was the human dental pulp isolated by enzymatic disintegration and analyzed by flow cytometry using the markers CD90, CD105, CD45, CD34, CD117, CD11b, CD3. Results: The ranks obtained from the positive markers for mesenchymal stem cells were, for CD90 (57.25% -66.21%), the CD105 marker was (2.69%-21.59%) and negative (0%) to the CD45 markers, CD34, CD11b, CD3, CD117. For cell viability, the range obtained from the 7-AAD marker was (77.11% -96.41%). Conclusions: The cell population of the human dental pulp presents multipotential expression with different percentages.